The Effects of Culture on Employee Performance (A Study in The Agent of Tele Account Management Unit, PT. Telecommunication Indonesia Regional VII Makassar) - Augustrianto, Agung; Rahayu, Agus; Adi Wibowo, Lili (International Journal of Engineering and Technology, 2018)
Organizational culture is an important factor affecting many aspects withinthe organization. Therefore, the aim of this research is to measure the relationship between organizational culture (such as clan, adhocracy, market, and hierarchy) and operational performance in the Tele Account Management Unit of PT. Telkom Indonesia Regional VII Makassar. Through the calculation using statistical tools, it was found that organizational culture had a simultaneous effect on the employee performance. And, the kind of culture implemented in this unit is the market culture.Â Â